Membangun Budaya Multikultural di Tengah Paham Keberagaman dan Fundamentalisme - Nazaruddin Nazaruddin (Medina-te : Jurnal Studi Islam, 2016)
Religious teachings had always taught and wanted peace and prosperity for all mankind, both life in this world and the afterlife. However, the social reality was found in the behavior and limited discourse and understanding, attitudes cons of peace and prosperity. Claims of truth (truth claims) and absolute validity, often used as the basis of legitimacy for doing the aggression of faith that was embraced against other religions.